An industrial systems analysis design study on Valdez Security and Investigation Agency, Inc. - Abadinas, John Erick H.; Cortez, Jervin D.; Licuanan, Kennedy V.; Rosacay, Marielle Anne DG
The Security Agency Industry in the Philippines has been around for over 50 years and currently there are about 483 security agencies in Metro Manila alone. It is second in terms of number of employees being hired with 105, 761 employees next to call center businesses and revenues realized all in all on this kind of sector is about 23.4 billion. Valdez Security and Investigation Agency, Inc. is a family-owned security agency located in Pasig City. The current workforce consists of 428 security guards. The company is considered a small-scale business with security guard services representing the bulk of its services offered. Currently, the company is providing its services to 68 clients ranging from NCR, Region I, Ill, and IV. Thorough documentation of the processes involving the operations division and financial department were done. Historical records were gathered and analysed. Some relevant data were not included within the agency's records thus interviews with the employees were conducted in order to gather these data. Problem Analysis was conducted to determine the areas where there are still room for improvements so as long as they do not go against the strategies set by the organization. In order to improve the overall system, the core problems were identified using a Stream Diagnostic Chart. Based on the chart, the core problems of the agency that result to the dissatisfaction of clients are 1) wide scope of job responsibilities of the operations manager, 2) job hiring process is done only in Metro Manila, and 3) competitors offering higher salary rates to security guards. In 2013, the agency lost two clients because of the dissatisfaction with the performance of the guards assigned to them even after several guard rotations resulting to the clients terminating their contracts with the agency and this had cost the agency a total of approximately PhP 600,000. Another core problem identified is the late payment of clients which causes the delay in bill collection. Due to this, the agency had to borrow from banks in order to continue its daily operations. In 2013, the agency lost approximately PhP 285,500 to loan interest rates. To address these problems, it was recommended that the agency hire an additional operations personnel in order to reduce the workload of the current operations manager. This will allow the operations manager to focus more on his job responsibilities. Another proposed solution was to build a satellite office in Tarlac. Since most of the applicants and clients of the agency are located there, it will greatly help the agency in screening and hiring new applicants and responding to detachment unit concerns. Lastly applying to a rebate system for clients who will pay on time was also proposed. Clients will gain points for every time they pay on time. They can choose to claim the cash equivalent of the accumulated points or use the points to pay for their next bill.This will entice the clients to pay their bills on time and will also entice potential clients to sign a contract with the agency.